Penciptaan Kriya Kayu untuk Hiasan Dinding Berbasis Ornamen Karo dengan Teknik Ukir - Yudea Agriva Tarigan; Sri Wiratma (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
Wood Craft is the art or skill in making an item that has a decorative function, Wood carving is an art that requires technical skills, also involves creativity in design and execution in its creation using wood as the main medium, in its creation the author made this work for wall decorations based on Traditional Karo Ornaments. The choice of Karo Ornaments in this work is because the author sees many types and uniqueness in their forms and in an effort to preserve Karo culture, especially in traditional ornaments. In the process the author uses carving techniques including recapan, buledan, krawinga, and krawengan. These techniques help the author in creating varied works. The stages of creation in this work the author uses the method proposed by S.P Gustami. The stages of the process of creating a work of art from this method are: 1. Exploration Stage 2. Design Stage 3. Realization Stage. The process of creating this work begins with making a design, transferring the design to wood media, carving wood according to the design pattern, sanding/smoothing the wood, and finishing with a layer of varnish. The result of this creation is 12 different sized craft works made of wood media for wall decorations based on Karo ornaments with carving techniques